MMP-2 associated imbalance of VEGF/Endostatin is linked to suppression of the PI3K/AKT/HIF-1α pathway in steroid-induced osteonecrosis of femoral head - Guangyang Zhang; Zhaopu Jing; Jialin Liang; Leifeng Lv; Xiaoqian Dang; Qichun Song (PLoS ONE, 2026)
Objective To investigate the role of matrix metalloproteinase-2 (MMP-2) and the imbalance between vascular endothelial growth factor (VEGF) and Endostatin in the pathogenesis of steroid-induced osteonecrosis of femoral head (SONFH). Methods Clinical samples and animal models were combined to systematically analyze the impact of VEGF/Endostatin imbalance on angiogenesis and osteogenesis. Clinical samples from SONFH patients and femoral neck fracture controls were analyzed for VEGF, Endostatin and MMP-2 expression. The SONFH model in C57BL/6J mice was established to evaluate the effects of an imbalanced VEGF/Endostatin axis on angiogenesis and osteogenesis, assessed by micro-CT based vascular imaging, calcein labeling, and bone density analysis. MMP-2 intervention experiments were conducted to explore its role in the VEGF/Endostatin ratio. Results Clinical data revealed significantly lower VEGF/Endostatin ratio (P < 0.001) and higher MMP-2 levels (P < 0.05) in necrotic regions of SONFH patients compared to the controls. In animal models, decreased VEGF/Endostatin ratio caused by Endostatin supplementation could further suppress angiogenesis and osteogenesis (P < 0.05). Mechanistically, MMP‑2 disrupts the VEGF/Endostatin balance by decreasing VEGF expression (P < 0.05) and increasing Endostatin levels (P < 0.05), which is associated with the suppression of PI3K/AKT/HIF‑1α pathway. Conclusions Our findings reveal that the imbalance of VEGF/Endostatin is a key driver of SONFH through impaired angiogenesis and osteogenesis. We further demonstrate that MMP‑2 contributes to this imbalance, likely linked to suppression of the PI3K/AKT/HIF‑1α pathway. These results support the VEGF/Endostatin ratio as a potential diagnostic biomarker and suggest that targeting MMP‑2 or Endostatin may represent promising therapeutic strategies.